Lingkup perkembangan sosial emosional: mengembangkan kemampuan sosial emosional anak kelompok a melalui metode bercerita di RA - Mustabsyiroh (Liberi, 2024)
Developing Social Emotional Skills of Group A Children through Storytelling Method at RA Masyithoh Miftahul Ulum. This research is motivated by the condition of the social emotional intelligence of children in the RA Masyithoh Miftahul Ulum group which is not yet optimal and still needs improvement. Some children have not been able to cooperate and control their emotions. To overcome this problem, a research was conducted on the development of Social Emotional Skills of Group A Children through the Storytelling Method at RA Masyithoh Miftahul Ulum. The purpose of this study is to improve the Social Emotional Skills of Group A Children through the Storytelling Method at RA Masyithoh Miftahul Ulum for six meetings. The learning improvement simulation has the following advantages and disadvantages: Advantages in the development simulation activities carried out: a) Simulation activities are carried out sequentially according to the RPPH and according to the theme; b) Activities and media used are appropriate to the age and characteristics of children aged 5-6 years; c) The media used are clear, interesting, and safe to use for children; and d) Teachers can master the material well, convey activities with clear and easy-to-understand language. 2) Weaknesses in the development simulation activities carried out: a) After the activity, the teacher did not provide reinforcement for children who were not yet able to complete the activity; and b) Rewards were given to children who were able to complete the activity, in the form of applause, star drawings, and high-fives from the teacher. The results of the study showed an increase in children's social and emotional development through storytelling methods at RA Masyithoh Miftahul Ulum, which initially achieved 0% BSB development to 87%.